2013
DOI: 10.1104/pp.113.216291
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast DNA Replication Is Regulated by the Redox State Independently of Chloroplast Division in Chlamydomonas reinhardtii

Abstract: Chloroplasts arose from a cyanobacterial endosymbiont and multiply by division. In algal cells, chloroplast division is regulated by the cell cycle so as to occur only once, in the S phase. Chloroplasts possess multiple copies of their own genome that must be replicated during chloroplast proliferation. In order to examine how chloroplast DNA replication is regulated in the green alga Chlamydomonas reinhardtii, we first asked whether it is regulated by the cell cycle, as is the case for chloroplast division. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…It has been reported that the activity of plastid POP is regulated by the redox state in the green alga Chlamydomonas reinhardtii . In vivo and in vitro experiments have indicated that plastid DNA replication was activated and inactivated by artificially changing the cellular redox state, though the POP protein level was constant [43]. In some primary plastid-bearing algae, it is therefore possible that dual-localized POPs are independently activated by the redox state in each organelle, causing kinetic differences in organellar DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the activity of plastid POP is regulated by the redox state in the green alga Chlamydomonas reinhardtii . In vivo and in vitro experiments have indicated that plastid DNA replication was activated and inactivated by artificially changing the cellular redox state, though the POP protein level was constant [43]. In some primary plastid-bearing algae, it is therefore possible that dual-localized POPs are independently activated by the redox state in each organelle, causing kinetic differences in organellar DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…In green plants, such as wheat, barley and pea, the plastid DNA number varies during the developmental stages [ 39 44 ], suggesting that the frequency of DNA replication and plastid division changes at each stage. Additionally, in the unicellular algae Chlamydomonas reinhardtii , which contain one plastid per cell, the plastid DNA replicates multiples times before plastid division [ 45 ]. In addition, phosphate limitation strongly affects the copy number of plastid DNA in Chlamydomonas [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Light has been shown to affect the amount of chloroplast DNA (ctDNA) during plant development (Shaver et al, 2008 ). Evidence for regulation of chloroplast DNA (ctDNA) by the redox state of cells has been reported in Chlamydomonas reinhardtii (Kabeya and Miyagishima, 2013 ), and similarly for yeast mitochondrial DNA (mtDNA; Hori et al, 2009 ).…”
Section: Introductionmentioning
confidence: 94%